Formulasi manajemen pemasaran produk Bank Syariah Indonesia (BSI) Cabang Bondowoso terhadap nasabah non-muslim - Islamiyah, Rofiatul; Nasrifah, Maula (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to analyze the marketing management formulation used by Islamic banks, especially PT. Bank Syariah Indonesia, Tbk Bondowoso Sub-Branch Office to attract Non-Muslim customers in using Savings Products and Financing Products, as well as the obstacles or obstacles they experience. This study uses a qualitative approach where research data collection through managing descriptive data, such as interview transcriptions and observations. The results of this study prove that in marketing its products to Non-Muslim Banks using several marketing techniques including PR marketing (Public Relations) and personal approaches (Personal Approach) or personal marketing (Personal Selling) and utilize the use of brochures, pamphlets, and banners for promotional media. . Meanwhile, the obstacles encountered were technical constraints such as the introduction of terms and the perception of the public who judged that Indonesian Islamic Banks were only intended for Muslims.